2001
DOI: 10.1016/s0093-691x(01)00532-5
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid concentrations in fluids from the bovine oviduct and uterus and in ksom-based culture media

Abstract: AabstractOviductal (OF) and uterine (UF) fluids from slaughterhouse bovine reproductive tracts selected around the pre-implantation period of embryo development were analyzed for twenty-four amino acids. Amino acid concentrations in the OF and UF fluids were compared with those in a base culture medium (KSOM) supplemented with either FCS or Minimum Essential Medium amino acids (MEM-aa) in addition to PVA, FCS or BSA. Concentrations of 23 amino acids in UF were significantly (P<0.05) higher than those provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 35 publications
2
32
2
Order By: Relevance
“…The identification of Gly as a highly abundant amino acid in female reproductive tract fluids is consistent with previous observations in cattle (Fahning et al 1967;Tiffin et al 1991;Moore and Bondioli 1993;Steeves and Gardner 1999;Elhassan et al 2001;Hugentobler et al 2007), sheep (Hill et al 1997;Moses et al 1997;Gao et al 2009b), horses (Engle et al 1984) and rabbits (Miller and Schultz 1987). The relatively high abundance of Gly in the uterine lumen across species suggests that it has an important role in embryo and/or conceptus development, and this is further supported by its abundance in the fetuses of swine throughout pregnancy (Wu et al 1999).…”
Section: Discussionsupporting
confidence: 88%
“…The identification of Gly as a highly abundant amino acid in female reproductive tract fluids is consistent with previous observations in cattle (Fahning et al 1967;Tiffin et al 1991;Moore and Bondioli 1993;Steeves and Gardner 1999;Elhassan et al 2001;Hugentobler et al 2007), sheep (Hill et al 1997;Moses et al 1997;Gao et al 2009b), horses (Engle et al 1984) and rabbits (Miller and Schultz 1987). The relatively high abundance of Gly in the uterine lumen across species suggests that it has an important role in embryo and/or conceptus development, and this is further supported by its abundance in the fetuses of swine throughout pregnancy (Wu et al 1999).…”
Section: Discussionsupporting
confidence: 88%
“…The free amino acid concentration and composition between bovine oviductal fluid and Eagle's formulation are obviously different. The total amount of Eagle amino acids (3.17mmol/L) is almost 10 times lower than that in bovine oviductal fluid (32.2mmol/L, Elhassan et al 2001;31.6mmol/L, Li et al 2003), and the concentration of several amino acid, such as glycine, is about 140 times lower (Elhassan et al 2001;Li et al 2003). Some non-protein amino acids, such as taurine (Tau), exist in both bovine and murine reproduction tract fluid (Elhassan et al 2001;Li et al 2003;Harris et al 2005) but are not contained in the Eagle formulation (Eagle 1959).…”
Section: Introductionmentioning
confidence: 79%
“…The total amount of Eagle amino acids (3.17mmol/L) is almost 10 times lower than that in bovine oviductal fluid (32.2mmol/L, Elhassan et al 2001;31.6mmol/L, Li et al 2003), and the concentration of several amino acid, such as glycine, is about 140 times lower (Elhassan et al 2001;Li et al 2003). Some non-protein amino acids, such as taurine (Tau), exist in both bovine and murine reproduction tract fluid (Elhassan et al 2001;Li et al 2003;Harris et al 2005) but are not contained in the Eagle formulation (Eagle 1959). Two research groups (McKiernan et al 1995;Bavister & Arlotto 1990;Lane & Gardner 1997;Lane et al 2001) have optimized the composition and concentration of amino acids in the culture media for hamster and mouse embryos.…”
Section: Introductionmentioning
confidence: 79%
“…It has previously been found that mouse oviductal fluid contains about 140 mM proline (Guerin et al, 1995), equivalent to 1-3% of total amino acids (Baltz, 2001). Proline is also present at significant concentrations in tubal fluid of cow and rabbit, to a lesser extent in sheep, but little in pig (Guerin et al, 1995;Elhassan et al, 2001). There was no information available about betaine in oviducts.…”
Section: Discussionmentioning
confidence: 98%